A Corpus-Based Lexical Profiling of English for Tourism Coursebooks: Pedagogical Register and Implications for ESP Materials Development - Anchalee Veerachaisantikul; Wara Chansin (Yayasan Visi Intan Permata, 2026)
The present study investigates the lexical features and pedagogical discourse of English for Tourism (EFT) textbooks widely used in Thai higher education. A specialized corpus of 15 textbooks (1,873 digitized pages) was constructed based on a nationwide examination of tourism and hospitality programs in four geographical regions of Thailand during the 2020–2021 academic year. WordSmith Tools were used to analyze the corpus on the basis of the course specifications of the Thai Qualifications Framework (TQF). The quantitative analysis revealed 181,303 tokens and 9,613-word types with an overall Type-Token Ratio (TTR) of 5.30%. The distributional analysis of the lexical categories showed that POS were distributed unevenly. The most dominant lexical category was the common and proper nouns (41.00%), offering a strong focus on tourism entities, professional roles, and operational concepts. The category of adjectives only represented 1.28% of the corpus, of which descriptive and evaluative adjectives were particularly scarce. The results point to the fact that the selected EFT textbooks mainly dealt with transactional and operational language, with limited exposure to persuasive and evaluative language that are crucial for the promotion of a destination and hospitality marketing. The study offers corpus-based evidence to improve ESP curricula, to evaluate the content of EFT textbooks, and to develop more balanced instructional materials for higher education settings.